Effects and neuroprotective mechanisms of vagus nerve stimulation on cognitive impairment with traumatic brain injury in animal studies: A systematic review and meta-analysis - Zhang, Han; Li, Chun-liu; Qu, Yun; Yang, Yu-xuan; Du, Juan; Zhao, Yu (Frontiers in Neurology, 2022)
Introduction: Cognitive impairment is the main clinical feature after traumatic brain injury (TBI) and is usually characterized by attention deficits, memory loss, and decreased executive function. Vagus nerve stimulation (VNS) has been reported to show potential improvement in the cognition level after traumatic brain injury in clinical and preclinical studies. However, this topic has not yet been systematically reviewed from published literature. In this study, we present a systematic review and meta-analysis of the effects of VNS on cognitive function in animal models of TBI and their underlying mechanisms. Methods: We performed a literature search on PubMed, PsycINFO, Web of Science, Embase, Scopus, and Cochrane Library from inception to December 2021 to identify studies describing the effects of VNS on animal models of TBI. Results: Overall, 9 studies were identified in animal models (36 mice, 268 rats, and 27 rabbits). An analysis of these studies showed that VNS can improve the performance of TBI animals in behavioral tests (beam walk test: SMD: 4.95; 95% confidence interval [CI]: 3.66, 6.23; p < 0.00001) and locomotor placing tests (SMD: -2.39; 95% CI: -4.07, -0.71; p = 0.005), whereas it reduced brain edema (SMD: -1.58; 95% CI: -2.85, -0.31; p = 0. 01) and decrease TNF-α (SMD: -3.49; 95% CI: -5.78, -1.2; p=0.003) and IL-1β (SMD: -2.84; 95% CI: -3.96, -1.71; p<0.00001) expression level in the brain tissue. However, the checklist for SYRCLE showed a moderate risk of bias (quality score between 30% and 60%), mainly because of the lack of sample size calculation, random assignment, and blinded assessment. Conclusion: The present review showed that VNS can effectively promote cognitive impairment and neuropathology in animal models of TBI. We hope that the results of this systematic review can be applied to improve the methodological quality of animal experiments on TBI, which will provide more important and conclusive evidence on the clinical value of VNS. To further confirm these results, there is need for high-quality TBI animal studies with a sufficient sample size and more comprehensive outcome evaluation.